Improvement Of Curve Construction Using Bi-Qt Bezier Curves And Approximation To Two Types Of Bezier Curves - Nordin, Mohamad Ekram (2024)
A new approach, namely an optimized bi-QT-Bezier, for fitting curves to given 2D, is proposed. The conventional approach includes additional constraints to uniquely determine the biarc. The proposed method integrates the formulation of a single biarc based on the Quadratic Trigonometric (QT)-Bezier curve with Particle Swarm Optimization (PSO). The proposed bi-QT-Bezier curve is advantageous in curve fitting as it provides an optimized value of α from the PSO method.